Design of intelligent braking system - Sidek, Shahrul Na'im; Salami, Momoh Jimoh Emiyoka (2000)
It is anticipated that a variety of cars with diversified features that include anti-lock braking system (ABS), traction control system (TCS), antiskid Steering, collision warning system (CWS) will be more commercially produced to satis@ the consumer needs in the near future. This is parallel to the trend of current technology of manufhcturing smart cars and the &sires of people who always want to have comfortable and safe ride in their vehicles. Mower this type of vehicles can fit much better into the intelligent highway that Malaysian government is planning to have in the near future. Consequently, there is a need to modify the current conventional braking system so as to make it work automatically. This paper considers the use of intelligent controller to achieve the above objective. To ensure high speed of system response, the DSP controller TMS320C24x with - fuzzy algorithm is used in the implementation of this new device. Results of simulation studies using the MATLAB have demonstrated the feasibility of this new system under investigation.